206 DIFFERNCES IN THE PREVALENCE AND DISTRIBUTION OF COLORECTAL POLYPS BASED ON GENDER AND ETHNICITY: A PROSPECTIVE STUDY. Issue 1 (1st January 2007) - Jain, S.; Johnson, W. D.; Minocha, A.
Abstract : Background: Previous research has suggested that gender and racial differences exist in the prevalence and distribution of polyps. Most of these studies were small, based on registries, or did not have enough African American (AA) representation. Our study evaluated these prospectively in an AA-predominant population. Methods: Patients receiving colonoscopy at a tertiary care medical center were enrolled prospectively. The polyps were defined as rectal, left-sided (sigmoid colon, descending colon, and splenic flexure), or right-sided (transverse colon, hepatic flexure, ascending colon, and cecum). The pathology was noted as hyperplastic or adenomas. Polyps ≥ 1 cm, with tubulovillous and villous histology, or with high-grade dysplasia were defined as advance adenomas. Results: Of 960 patients enrolled, 929 patients who were of Caucasian white (CW) or AA ethnicity were included; 59.5% (553) were AA and 40.5% (376) were CW; 41.2% of AAs had polyps and 45% of CWs had polyps ( p = NS). CW had significantly more hyperplastic polyps than AA (18.4% vs 13.6%, p = .0478). Males were more likely to have rectal adenomas than females. CW males were five times more likely than AA females to have rectal adenomas and 2.9 times more likely to have right-sided adenomas (OR 5.0, CI 1.9-12.1 and OR 2.9, CI 1.1-7.2). CWs had significantly more adenomas in rectum compared with AAs. Of the patients with advance adenomas, CWs were more likely to have them in the rectum compared with AAs (36% vs 11.9%, p = .01). Conclusions: The overall prevalence of polyps was similar in AAs and CWs. CWs are more likely to have hyperplastic polyps. There is a higher prevalence of rectal adenomas and advance adenomas in CWs. Men are more likely to have rectal adenomas than women. Our results suggest differences in pathogenesis dependent on ethnic background and gender and warrant further studies.